Gaya Komunikasi Selebgram Cut Bul dalam Product Endorsment di Instagram - Maghfrah; Masriadi (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2024)
Indirect communication style can also determine a person's self-image. The positive image a person has will influence their interest and the number of other people who like them. Indirectly, it can also play a role in attracting public attention during the endorsement process. On the other hand, if someone's communication style only gives a negative image of themselves, then many people will reject and be uninterested in the product offered in the endorsement. The research method uses descriptive qualitative methods. The research results show that this communication style is characterized when the Cutbul celebgram is promoting or endorsing a product and the celebgram gives orders to its followers to follow the online shop account they are promoting, and this communication style is also an information function which is characterized by the information provided by Instagram celebrities like when promoting products on Instagram that the product they are reviewing is really a good and quality product. From the communication style that exists on the Cutbul program, there are several factors that influence the formation of this communication style. Influencing factors are physical condition, role, historical context, chronology, language and obstacles.